Nursing of one case of lower extremity arteriosclerosis obliterans treated by Chinese herbal ointment and massage combined with intradermal acupuncture (中药膏摩联合皮内针治疗1例下肢动脉硬化闭塞症的护理体会) - DONG Yuxia (董玉霞); WEI Yongchun (魏永春); NIU Shaohui (牛少辉); LIU Jinjing (刘津京); E Haiyan (鄂海燕); ZHI Hui (智慧); WANG Yali (王亚丽); TANG Ling (唐玲); QIN Shasha (秦沙沙) (中西医结合护理)
This paper summarized the nursing experience of a case of lower extremity arteriosclerosis obliterans treated with Chinese herbal ointment and massage combined with intradermal acupuncture. Based on the nursing evaluation on pain, skin temperature, intermittent claudication, arteriopalmus of dorsalis pedis artery and other indicators, the application of Chinese herbal ointment and massage combined with intradermal acupuncture is effective to relieve the symptom of the lower-limb ischemia. (本文总结中药膏摩联合皮内针辅助治疗1例下肢动脉硬化闭塞症住院患者的护理体会。在完善疼痛、皮肤温度、间歇性跛行、足背动脉搏动等指标的评估的基础上, 运用中药膏摩联合皮内针辅助治疗, 能有效改善患者下肢缺血症状和体征。)